Design and rationale of the COVID-19 Critical Care Consortium international, multicentre, observational study. Issue 12 (2nd December 2020) - Li Bassi, Gianluigi; Suen, Jacky; Barnett, Adrian Gerard; Corley, Amanda; Millar, Jonathan; Fanning, Jonathon; Lye, India; Colombo, Sebastiano; Wildi, Karin; Livingstone, Samantha; Abbate, Gabriella; Hinton, Samuel; et al.
Abstract : Introduction: There is a paucity of data that can be used to guide the management of critically ill patients with COVID-19. In response, a research and data-sharing collaborative—The COVID-19 Critical Care Consortium—has been assembled to harness the cumulative experience of intensive care units (ICUs) worldwide. The resulting observational study provides a platform to rapidly disseminate detailed data and insights crucial to improving outcomes. Methods and analysis: This is an international, multicentre, observational study of patients with confirmed or suspected SARS-CoV-2 infection admitted to ICUs. This is an evolving, open-ended study that commenced on 1 January 2020 and currently includes >350 sites in over 48 countries. The study enrols patients at the time of ICU admission and follows them to the time of death, hospital discharge or 28 days post-ICU admission, whichever occurs last. Key data, collected via an electronic case report form devised in collaboration with the International Severe Acute Respiratory and Emerging Infection Consortium/Short Period Incidence Study of Severe Acute Respiratory Illness networks, include: patient demographic data and risk factors, clinical features, severity of illness and respiratory failure, need for non-invasive and/or mechanical ventilation and/or extracorporeal membrane oxygenation and associated complications, as well as data on adjunctive therapies. Ethics and dissemination: Local principal investigators will ensure that the study adheres to all relevant national regulations, and that the necessary approvals are in place before a site may contribute data. In jurisdictions where a waiver of consent is deemed insufficient, prospective, representative or retrospective consent will be obtained, as appropriate. A web-based dashboard has been developed to provide relevant data and descriptive statistics to international collaborators in real-time. It is anticipated that, following study completion, all de-identified data will be made open access. Trial registration number: ACTRN12620000421932 (http://anzctr.org.au/ACTRN12620000421932.aspx ).